1989
DOI: 10.1037/0021-843x.98.2.107
|View full text |Cite
|
Sign up to set email alerts
|

Probability of relapse after recovery from an episode of depression.

Abstract: Examined relapse rates in those individuals who have experienced an episode of unipolar depression as a function of the number of previous episodes, gender, age at onset of the episode (less than 40 vs. greater than 40), time since a previous episode, and depression level at time of interview. From of 6,742 participants, 2,046 were interviewed; of these, 1,130 had at least one, 513 reported a second and 173 reported a third episode. The probability for relapse was positively related to number of previous episo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
82
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(89 citation statements)
references
References 18 publications
6
82
0
1
Order By: Relevance
“…However, their participants varied in the number of In addition, the men and women in their sample did not differ in the number of recurrent episodes they had during the follow-up period. The non-significant role of gender in the recurrence of depression has also been replicated in other studies (Coryell, Endicott, & Keller, 1991;Kovacs, 2001;Kovacs et al, 1984;Lewinsohn, Zeiss, & Duncan, 1989).…”
Section: Gendersupporting
confidence: 59%
See 1 more Smart Citation
“…However, their participants varied in the number of In addition, the men and women in their sample did not differ in the number of recurrent episodes they had during the follow-up period. The non-significant role of gender in the recurrence of depression has also been replicated in other studies (Coryell, Endicott, & Keller, 1991;Kovacs, 2001;Kovacs et al, 1984;Lewinsohn, Zeiss, & Duncan, 1989).…”
Section: Gendersupporting
confidence: 59%
“…However, their participants varied in the number of In addition, the men and women in their sample did not differ in the number of recurrent episodes they had during the follow-up period. The non-significant role of gender in the recurrence of depression has also been replicated in other studies (Coryell, Endicott, & Keller, 1991;Kovacs, 2001;Kovacs et al, 1984;Lewinsohn, Zeiss, & Duncan, 1989).The failure of gender to be associated with the depression recurrence has also been replicated in larger, epidemiological samples. Wainwright and Surtees (2002), for example, studied 3491 adults (aged 48-79) in the European Prospective Investigation into Cancer and Nutrition (EPIC) study and found that men and women with a history of depression did not significantly differ in risk of recurrent depression (60.4% of women and 60.1% of men had had more than one episode).…”
mentioning
confidence: 58%
“…He pointed out that the empirical hazard~ction gives no basis for ruling out the original exponential assumption, since mixtures of exponentials can give exactly the kind of hazard functions that Proschan observed. Thus, the shape of the hazard function is am~iguo~s with.regard to the original distribution when a mixture I~possible, Hazard-function analyses are becoming more common in areas of psychology apart from RT research.~or example, Lewinsohn, Zeiss, and Duncan (1989) tallied the frequency ofepisodes ofunipolar dep~ssion.for~ev eral clinical groups. All groups showed an mcreasmg likelihood ofexperiencing an episode over time, as reflected in an increasing hazard function; however, they observed that men with only one prior depressive episode eventually declined in vulnerability to a second episode.…”
mentioning
confidence: 99%
“…En plus des taux plus élevés observés, chez les femmes, les études révèlent que le désordre apparaît plus jeune (Sorenson, Rutter & Aneshensel, 1991) et est associé à une plus grande probabilité de rechute (Lewinsohn, Zeiss & Duncan, 1989;Lewinsohn, Roberts, Seeley, Rohde, Gotlib& Hops, 1994), à l'exception de l'étude de Coryell, Endicott et Keller (1991) qui ne démontre pas de différences de genre à propos du taux de rechute.…”
Section: La Dépression Et Les Différences Liées Au Genre Chez Les Adounclassified